Handling culture medium composition for optimizing plant cell suspension culture in shake flasks - Fidemann, Tiago [UNESP]; de Araujo Pereira, Gabriela Aparecida [UNESP]; Heluy, Tárik Reis [UNESP]; Gallego, Rodrigo Boccoli [UNESP]; Bertão, Mônica Rosa [UNESP]; da Silva, Regildo Márcio Gonçalves [UNESP]; Fernández Núñez, Eutimio Gustavo (Springer Nature, 2018)
This work aimed to optimize statistically the culture medium composition for cell plant suspension culture using as a model Capsicum baccatum L. var. pendulum cells. The cell growth was maximized as well as the secondary metabolite yields with antioxidant activity, which could find applications in pharmaceutical and food industries. A Box–Behnken statistical design was utilized to optimize the basal Murashige and Skoog medium, which is widely used in plant cell culture. Three relevant ingredients, saccharose (A, 15–45 g L−1), KH2PO4 (B, 0.085–0.255 g L−1) and KNO3 (C, 0.95–2.85 g L−1) were considered. The cell growth index as well as antioxidant activity, total phenolic compounds and flavonoids from dry extracts (DE) derived of cell cultures, were determined. Growth index (GI) and flavonoids content (F) were sensitive to the changes in nutrient composition in culture medium, and they were modeled statistically according to modified quadratic (GI = 1.76 + 0.59 A - 0.32 B - 0.42 AC) and two-factor interaction (F (mg of rutin / g DE) = 0.88 + 0.35 AC - 0.29 BC) models, respectively. Antioxidant activity and total polyphenols were independent of the nutrient concentrations within the range under study. The optimized culture medium composition was defined for two approaches: maximization of the cell growth (45 g L−1 saccharose, 0.09 g L−1 KH2PO4, 0.95 g L−1 KNO3) and maximization of flavonoids production (45 g L−1 saccharose, 0.09 g L−1 KH2PO4, 2.85 g L−1 KNO3). According to the current results, other elicitation strategies should be assessed to make this bioprocess more efficient for manufacturing secondary metabolites with antioxidant activity from suspension culture of Capsicum baccatum L. var. pendulum cells.
Keywords: Bioprocess optimization; Capsicum baccatum L. var. pendulum; Plant cell culture; Polyphenolic compounds; Suspension culture